Immune response to a model shared placenta/tumor-associated antigen reduces cancer risk in parous mice†. Issue 1 (22nd December 2016) - Jasti, Susmita; Farahbakhsh, Mina; Nguyen, Sean; Petroff, Brian K.; Petroff, Margaret G.
Abstract: During human pregnancy, paternally inherited antigens expressed by the fetal–placental unit can elicit expansion of antigen-specific CD8+ T cells. These cells can persist for years as memory T cells, but their effects on long-term maternal health are unknown. Shared placenta/tumor-associated antigens are expressed by placenta and tumors, but are minimally expressed or absent in normal adult tissues. We hypothesized that maternal T cells elicited against these antigens can alter risk of cancers expressing the same antigen after pregnancy, and tested this in mice using chicken ovalbumin (OVA) as a surrogate shared placenta/tumor antigen. Hemizygous OVA transgenic males were bred to wild-type C57BL/6 females (H2b haplotype) such that the fetuses inherited and expressed OVA. Maternal OVA/H2K b -specific CD8+ T cells became detectable during gestation, and persisted in some animals for up to 24 weeks. To determine whether these cells might influence growth of OVA-expressing tumors in OVA-bred females, E.G7-OVA thymoma cells were inoculated subcutaneously in OVA-bred, wild-type bred, and virgin females, and monitored for growth. OVA-bred mice had prolonged survival as compared to virgin mice and the progression of tumors was delayed in comparison to wild-type bred and virgin females. Thus, paternally inherited OVA antigen elicited a CD8+ T cell response during pregnancy that was associated with delayed growth of OVA-expressing tumors following pregnancy. These data suggest a possible role of antigen-specific T cells in protecting parous females against tumors bearing shared placenta/tumor antigens. Summary Sentence: Gestational exposure of shared placenta/tumor-associated antigen may induce antigen-specific T cells, which may lower cancer risk against tumors bearing same antigen.